2009
DOI: 10.1021/jf901678v
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Fruit Volatiles in the Progeny of a ‘Royal Gala’ × ‘Granny Smith’ Apple (Malus×domestica) Cross

Abstract: Volatile flavor compounds from the fruit of the progeny of two apple (Malus x domestica) cultivars with distinctive flavor and volatile profiles, 'Royal Gala' and 'Granny Smith', were measured by headspace gas chromatography-mass spectrometry over two fruiting seasons. Principal component analysis separated the volatile profiles into two groups according to the amounts produced of butyl, 2-methybutyl, pentyl, and hexyl acetates and of ethyl butanoate, butanol, 2-methylbutanol, and hexanol. Fruit containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 38 publications
(72 reference statements)
7
55
0
Order By: Relevance
“…Similar observations have been reported in apple (Dunemann et al 2009;Rowan et al 2009b), strawberry (Olbricht et al 2008;Zorrilla-Fontanesi et al 2012), rose (Spiller et al 2010), and in non Rosaceae species, such as tomato (Tadmor et al 2002;Zanor et al 2009), grape (Doligez et al 2006), andeucalypt (O'Reilly-Wapstra et al 2011).…”
Section: Linkage Mappingsupporting
confidence: 76%
“…Similar observations have been reported in apple (Dunemann et al 2009;Rowan et al 2009b), strawberry (Olbricht et al 2008;Zorrilla-Fontanesi et al 2012), rose (Spiller et al 2010), and in non Rosaceae species, such as tomato (Tadmor et al 2002;Zanor et al 2009), grape (Doligez et al 2006), andeucalypt (O'Reilly-Wapstra et al 2011).…”
Section: Linkage Mappingsupporting
confidence: 76%
“…For example, four variables obtained by HPLC/ DAD/MS analysis performed on skin, Q-rhamno-glucoside (H1-S), Q-galactoside (H2-S), Q-glucoside (H3-S), and total flavonols (H8-S), shared the same area (i.e., the negative range of PC2) with apples grown in Tuscany (CON-B) with conventional agronomic management; in the skin of such fruits, in fact, the highest content of those compounds was found. Among the original variables that contributed to the PCs, it is worth noting that the first PC (that described 54.24% of variability) was defined mainly by analytical parameters obtained from the analysis of pulp, especially flavonols (Table 4), while parameters obtained from the [13,15,16,29,31,33,39] skin contributed to the definition of the second PC, especially caffeic acid derivatives.…”
Section: Principal Component Analysis On Hplc Datamentioning
confidence: 99%
“…Together with esters, α-farnesene is one of the most characteristic and abundant volatile compounds emitted by apples [13] and has been proposed for cultivar classification [40]. This terpenoid is normally found in stored apples [39], and it is expected to increase significantly with postharvest ripening, starting from the first few days [17]. Other authors [15,16,33] have tentatively identified m/z 149.100 as estragole, a terpenoid ether associated with a spice-like or aniseed aroma in apple, mainly produced during post harvest maturation as well.…”
Section: Ptr-tof-ms Spectra Analysismentioning
confidence: 99%
“…Apple is a self-incompatible and highly heterozygous species, with cross breeding resulting in diverse progeny, of which few are superior to their parents. Therefore, apple breeding usually involves backcrossing, to enhance traits of interest from high-quality parents into new cultivars (Rowan et al, 2009). Traditional cross breeding has generated numerous cultivars, such as 'Gala', 'Fuji', 'Cripps Pink', and 'Qinguan'.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods offer more efficient tools for cultivar improvement, particularly for fruit trees with long juvenile periods (Rowan et al, 2009). MAS has been widely implemented for plant breeding, and is particularly useful in cases where the traits of interest show recessive or polygenic inheritance, and/or are difficult or impossible to select directly (Yeam et al, 2005).…”
Section: Introductionmentioning
confidence: 99%